Economic Organization with Limited Communication - Townsend, Robert M. (American Economic Review, 1987)
This paper presents formal, stylized representation of communication-accounting systems: oral assignment, portable object, written message, and telecommunication systems are considered. The environments that allows this formalization are characterized by spatial separation, private information, and a need to keep track of past actions, transfers, and shocks.